Progrès et développement économique au Chili durant la République conservatrice (1830-1861) - Jérôme Louis (Les Cahiers ALHIM)
Conservatives won over the Liberals at Lircay in 1830. The Portales Constitution and victory against the Peru-Bolivian Confederation (1836-1839) allowed Chile to control South Pacific. Valparaiso became the main harbor for the nascent Chilean navy, and opened up to international trade. But the estate was in debt (£ 1 million) since 1822. To pay off, government established estanco and relied on customes declaration. Economy of Chile was neomercantilism just like Iberic tradition. Between 1830 en 1850, tariffs were preserved. Meanwhile French merchants introduced European products. Colonization grew up. German communities prospered. The indian territories were encroaching. Around 1856, Chilean economy was starting to falter. The 1857 crisis was caused by a credit and money crunch. Agricultural exports declined. The estate became shareholder in the railway, major legal disputes and civil war were now spreading like wildfire. On September 18th1861, the Liberals came to power in Chile.